An economical approach combining vacuum assisted soft imprinting and hydrothermal treatments to fabricate lotus leaf-like biomimetic hierarchical TiO2 structures. (13th July 2018) - Chen, Hongpeng; Wu, Xingda; Chen, Quan; Lv, Qunsong; Tang, Nan; Chen, Jiayi
Abstract: Here we report an low-cost method for fabricating 3D hierarchical TiO2 films with lotus-leaf-like micro/nano structures. With some low pressure provided by two middle-sized binder clips, the microscale pillar arrays of lotus leaf could be easily imprinted into the TiO2 sol film. In addition, if a low vacuum was introduced into the imprinting process, the complex laminar sub-microstructure on the micro pillars could also be duplicated with high fidelity. Hierarchical TiO2 micro/nano-structures were subsequently fabricated by the hydrothermal growth of TiO2 nanorods on the micro-structured TiO2 film. SEM observation and XRD analysis revealed that the micro-structured TiO2 film was anatase phase, which served as a nucleation layer for the growth of rutile TiO2 nanorods. This hierarchical surface exhibited a WCA of 155° after surface fluoroalkylsilane modification.